Occurrence and distribution of sesamoid bones in squamates: A comparative approach - Jerez, Adriana de Los Angeles (2010)
Sesamoids are defined as skeletal elements that develop within a continuous band of regular dense connective tissue (tendon or ligament) adjacent to an articulation or joint. In this work, we discuss developmental data on two squamate species, provide data on the onset of the squamate sesamoids and the muscles they are associated to. Our results show that Mabuya mabouya and Liolaemus albiceps exhibited rather similar ontogenetic patterns and that the first sesamoids appear in embryos. The ossifying sesamoid timing is different between M. mabouya and L. albiceps, being faster in the former. In adults, we found 41 sesamoids, considering both fore and hindlimbs. We did not find any intrataxonomic differences, or any differences between the right and left side of the specimens in relation to the sesamoid presence. We recognize four types of sesamoids: (1) embedded sesamoids; (2) interosseus sesamoids; (3) glide sesamoids; and (4) supporting sesamoids. A table is included with a preliminary survey of the sesamoid distribution pattern in 10 Squamate clades.